Indicadores de risco para surdez em neonatos de uma maternidade da cidade de São Paulo nos anos de 1995 e 2005 - Lopes, Monique Kelly Duarte (2010)
Introduction: the data submitted by the Surveillance Epidemiological Center of the State of São Paulo, Brazil, pointed out that the number of children, particularly with infectious diseases increases each year. Some of these diseases are considered as indicators of risk for hearing. To know their occurrence is important in order to support official programs for hearing loss prevention and hearing conservation. Objective: to analyze and compare the occurrence of risk indicators for hearing in a period of 10 years (1995-2005) in a public maternity of São Paulo, Brazil. Method: It is a retrospective and quantitative study, based on collected data of newborn records of a public maternity of São Paulo. Records of babies born between January and December of 1995 and 2005 and that presented deafness risk indicators, such as: prematurity, low weight and asphyxia, and/or, have suspected or confirmed diagnosis of TORSCH-A group infection (toxoplasmosis, congenital rubella, syphilis, cytomegalovirus, Herpes and HIV+) were included. Results: from all the babies records, were considered 565 children born in 1995, and 1047 in 2005. Among the risk indicators for deafness analyzed in two years, it was observed that there was significant difference for the indicator prematurity, being the largest percentage of premature children in 1995 (p<0,001); there was no significant difference between the percentages of low weight indicator occurrence in 1995 and 2005 (p =-0,209), and there was significant difference between the percentages of children with asphyxia in two years (p = 0,027). The higher percentage of occurrence was in 1995. The risk indicators: prematurity, low weight and asphyxia were more frequent than toxoplasmosis, syphilis and HIV. The compared analysis of concurrency of these 3 risk factors has been reviewed and compared, in 1995, 1.2% of children did not present any of 3 risk indicators, while, in 2005, that percentage was 9.1%. In 1995, we observed the largest percentage of children with prematurity and low weight (28.9%), while in 2005 it was only low-weight (31.1%). It was also noted that in 1995 there was simultaneous occurrence of 3 risk factors in 7.3% of children, while that in 2005 the percentage was 3.2%. There is no significant difference between the associated percentages for prematurity, low weight and asphyxia in two years (p<0,001). In two years, the largest number of indicators observed in one child was 3. Most of the babies presented at least one risk indicator (57.1% in 1995 and 69.4% in 2005). Conclusion: Children born in 1995 tended to have a greater number of indicators of risk than those born in 2005 (p<0,001)